Temperature of Eggshell, Weight Loss, and Air Sac on Hatched Local Duck Eggs During Incubation - Yusuf Kurniawan; Rukmiasih Rukmiasih; Mokhamad Fahrudin; Peni Soeprapti Hardjosworo (Faculty of Animal Science, Universitas Gadjah Mada, 2018)
The study was conducted to analyze the characteristic of eggs (temperature of eggshell, weight loss, and air sac alteration) at various hatching period of local duck hatched (H) and unhatched (UH) at the final observation, and to find out the effective time for estimating the life of embryo during the end of incubation. A total of 146 eggs were incubated and observed between 1 and 25 days of incubation (DOI). The results of weight loss and air sac change showed a significant difference (P<0,05) between H and UH eggs on 7 to 25 DOI, while the temperature of eggshell was only different on 25 DOI. The average characteristic of H group (temperature of eggshell, weight loss, and air sac alteration) on 25 DOI was recorded 38,46oC, 11,84%, and 51,03%, respectively. It can be concluded that 3 characteristics of eggs influence hatchability of local duck. Weight loss and air sac alteration parameters can be applyed to estimate the hatched eggs between 7 and 25 DOI, but the temperature of eggshell can be administrated after 25 DOI.